Leading a Large‐Scale Distributed Social Enterprise: How the Leadership Culture at Goodwill Industries Creates and Distributes Value in Communities. Issue 3 (12th January 2017) - Gibbons, Jim; Hazy, James K.
Abstract : Distributed social enterprises with national or international footprints face unique management challenges. To cast a lens on these challenges, we analyze the case of the US‐based social enterprise Goodwill Industries, a century‐old, hybrid nonprofit organization with annual business‐related revenue of more than $5.5 billion. The economic benefits that accrue from this business are used to support a social mission that has continued to evolve for more than 100 years. We explore how Goodwill is organized and how its management works to continually balance economic and social objectives to facilitate long‐term success.